2016
DOI: 10.1016/j.appet.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Latina mothers' influences on child appetite regulation

Abstract: Parents influence child weight through interactions that shape the development of child eating behaviors. In this study we examined the association between maternal autonomy promoting serving practices and child appetite regulation. We predicted that maternal autonomy promoting serving practices would be positively associated with child appetite regulation. Participants were low-income Latino children—a group at high risk for the development of childhood obesity. A total of 186 low-income Latina mothers and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…It has been argued that much of the association of feeding styles and feeding practices with children's weight status is due to the parenting behaviors being in response to their child's eating behaviors, which may actually drive the association [ 39 ]. In the analysis presented here, three child eating behavior characteristics (food responsiveness, emotional overeating, and satiety responsiveness) previously linked to either parent food parenting practices or child weight status in cross-sectional studies [ 29 , 30 ] were assessed. While satiety responsiveness was significantly negatively correlated with the child's BMI z -score at Time 1, none of these child eating behaviors correlated with the BMI z -score at Time 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that much of the association of feeding styles and feeding practices with children's weight status is due to the parenting behaviors being in response to their child's eating behaviors, which may actually drive the association [ 39 ]. In the analysis presented here, three child eating behavior characteristics (food responsiveness, emotional overeating, and satiety responsiveness) previously linked to either parent food parenting practices or child weight status in cross-sectional studies [ 29 , 30 ] were assessed. While satiety responsiveness was significantly negatively correlated with the child's BMI z -score at Time 1, none of these child eating behaviors correlated with the BMI z -score at Time 2.…”
Section: Discussionmentioning
confidence: 99%
“…The CEBQ has been used successfully in low-income samples [ 28 ]. To reduce the number of variables in the analyses, the three subscales related to the self-regulation of caloric intake—food responsiveness (e.g., my child is always asking for food), emotional overeating (e.g., my child eats more when worried), and satiety responsiveness (e.g., my child gets full before his/her meal is finished)—were used in this study as they have been linked to food parenting practices and child weight in Hispanic samples [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parents influence a child’s weight through interactions that shape the development of child eating behaviors. Maternal autonomy promoting serving practices is positively associated with child appetite regulation [ 58 , 63 ].…”
Section: Practice Six: Respect For the Child’s Appetitementioning
confidence: 99%
“…Maternal reports of child higher FR and lower SR have been associated with higher weight status (Carnell & Wardle, 2008, 2009; Domoff, Miller, Kaciroti, & Lumeng, 2015; Sánchez, Weisstaub, Santos, Corvalán, & Uauy, 2016; Sleddens, Kremers, & Thijs, 2008; Spence, Carson, Casey, & Boule, 2011; van Jaarsveld, Boniface, Llewellyn, & Wardle, 2014; Viana, Sinde, & Saxton, 2008; Webber, Hill, Saxton, Van Jaarsveld, & Wardle, 2009). Yet, studies that have examined associations among maternal reports of child FR and EAH among diverse cohorts of preschoolers and toddlers have found null results (Carnell & Wardle, 2007; Garcia, Power, Fisher, O’Connor, & Hughes, 2016; Mallan et al, 2014). Similarly, studies that have accessed the associations between maternal reports of child SR and EAH in these samples have also mostly found null results (Garcia et al, 2016; Mallan et al, 2014), with an exception of one study of preschoolers and older children that showed EAH was associated with SR (Carnell & Wardle, 2007).…”
mentioning
confidence: 99%
“…Yet, studies that have examined associations among maternal reports of child FR and EAH among diverse cohorts of preschoolers and toddlers have found null results (Carnell & Wardle, 2007; Garcia, Power, Fisher, O’Connor, & Hughes, 2016; Mallan et al, 2014). Similarly, studies that have accessed the associations between maternal reports of child SR and EAH in these samples have also mostly found null results (Garcia et al, 2016; Mallan et al, 2014), with an exception of one study of preschoolers and older children that showed EAH was associated with SR (Carnell & Wardle, 2007). One possible reason for this lack of associations could be that assessing child eating behaviors using parental reports has limitations, for example reporter bias.…”
mentioning
confidence: 99%